2005
DOI: 10.1126/science.1106974
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Cause of an Ancient Adaptation

Abstract: Phylogenetic analysis reveals that the use of nicotinamide adenine dinucleotide phosphate (NADP) by prokaryotic isocitrate dehydrogenase (IDH) arose around the time eukaryotic mitochondria first appeared, about 3.5 billion years ago. We replaced the wild-type gene that encodes the NADP-dependent IDH of Escherichia coli with an engineered gene that possesses the ancestral NAD-dependent phenotype. The engineered enzyme is disfavored during competition for acetate. The selection intensifies in genetic backgrounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
157
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 129 publications
(162 citation statements)
references
References 26 publications
5
157
0
Order By: Relevance
“…For several cases, however, ancestral molecules have been engineered, allowing studies of functional changes in the past (6). These analyses demonstrate that functional changes actually occurred, but they do not necessarily mean that the new characters were adaptive (7). To complicate the matter further, evolutionary changes are not always unidirectional and ancestral phenotypes may reappear during evolution (8,9).…”
mentioning
confidence: 99%
“…For several cases, however, ancestral molecules have been engineered, allowing studies of functional changes in the past (6). These analyses demonstrate that functional changes actually occurred, but they do not necessarily mean that the new characters were adaptive (7). To complicate the matter further, evolutionary changes are not always unidirectional and ancestral phenotypes may reappear during evolution (8,9).…”
mentioning
confidence: 99%
“…Only recent efforts have aimed at identifying changes in sequence and structure that affect fitness within a defined protein fold (4, 7, 8, 10, 11). The identification of such structural traits acquired through evolution allows both the reconstruction of ancestral genes (7,8,12) and the prediction of future evolutionary events (5,13). The latter approach could be immensely valuable for anticipating the molecular features that might enhance bacterial resistance to antibiotics, thereby informing strategies to combat this clinical threat.…”
mentioning
confidence: 99%
“…P rotein evolution is crucial for organismal adaptation and fitness (1)(2)(3)(4)(5)(6)(7)(8). This process takes place by shaping a given 3-dimensional fold for its particular biochemical function within the metabolic requirements and constraints of the environment.…”
mentioning
confidence: 99%
“…However, no conclusive experimental evidence has been provided to support this theory up to now. Site-directed mutagenesis experiments have shown that the coenzyme specificity of MDH is determined by a limited number of amino acid residues (Tomita et al, 2005(Tomita et al, , 2006b, and that the coenzyme specificity of some dehydrogenases could be shifted by alteration of a few specific amino acids in the enzyme to adapt to the environment during the enzyme's evolution (Zhu et al, 2005). In the present study, we altered the coenzyme specificity of MDH from a Gram-positive bacterium S. coelicolor A3(2).…”
Section: Discussionmentioning
confidence: 99%